Review of Law Enforcement in Indonesia - Munawar, Sepa (AHKAM, 2023)
Law enforcement is the process of making efforts to enforce or function legal norms in a real way as a guide for behavior in traffic or legal relations in social and state life. The problem of law enforcement in society is very urgent. Considering the existence of the law itself cannot be separated from social and state life. The purpose of this study is to find out what law enforcement is, the importance of law enforcement, the low level of law enforcement in Indonesia and the various factors that surround it. The method that the author uses is a type of normative legal research (Normative Legal Research), which is "a type of research carried out by examining library materials or secondary data. The results showed that law enforcement in Indonesia still cannot be carried out properly. This is evidenced by the many problems faced in enforcing the law. These problems, for example, there has been no unification of laws and regulations and legal certainty, the decline in the authority of law enforcement officials, judicial systems that have not been implemented effectively and efficiently and the low legal awareness culture of the Indonesian people. The efforts that need to be made to elevate the authority of the law and uphold the rule of law include it must be carried out or formulated for legal unification or its exact mapping, improving the moral and professional quality of law enforcement officers and improving systems.